Analisis Pengaruh Kompensasi dan Pelatihan Kerja Terhadap Produktivitas Karyawan Ajb Bumiputera 1912 - Sri Waluya; Erliza (Mulia Pratama, 2022)
In this modern era the development of science and technology more advanced, it encourages the rapid development of companies, so that the necessary changes - changes that must be done by the company. In this case the company has the support of human resources to promote the company, one of them is the employee, where the provision of compensation and job training is very influential on employee productivity, for that the author is interested to take the title "Analysis Influence Compensation and Job Training Employee Productivity AJB Bumiputera 1912, has a formulation of the problem of how much influence the compensation and job training on employee productivity AJB Bumiputera 1912. The purpose of this study was to determine the effect of compensation and job training on employee productivity. This research uses data collection method through literature research and field research where field research is done by direct observation (observation), interview and using questionnaire (questionnaire), questionnaire tested using validity test and reliability test whether questionnaire is feasible or not used as research , the type of sample used is the sample area technique, to determine the object of research for the object of research is not too widespread where the sample used is 64 employees in the claim department. Data were analyzed using qualitative and quantitative methods using analytical tools such as classical assumption test, multiple linear regression analysis and Goodnes of Fit test. Using SPSS Version 22. Based on data analysis, it can be concluded that in the partial test (t test) through SPSS Version 22 it can be seen that the result of the sig value for the compensation variable (X1) on employee productivity shows Thitung > Ttabel 3.528 > 1,999. So the compensation effect on employee productivity. The result of testing of job training variable (X2) on employee productivity (Y) shows Thitung < Ttabel 1,854 < 1,999. So job training has no effect on employee productivity. Based on the result of thorough testing (Test f) through SPSS Version 22 seen from sig result 0.000 < 0,05. Then the independent variables of compensation and job training (independent) have a significant effect on the dependent variable of employee productivity. The overall result of data management using SPSS Version 22 can be concluded that the independent variable of compensation (X1) has positive and significant effect on employee productivity while job training variable (X2) has no positive and significant effect on employee productivity dependent variable (Y) AJB Bumiputera 1912.